Individual Differences in Toddlers' Prosociality: Experiences in Early Relationships Explain Variability in Prosocial Behavior. Issue 6 (7th November 2016) - Newton, Emily K.; Thompson, Ross A.; Goodman, Miranda
Abstract : Latent class logistic regression analysis was used to investigate sources of individual differences in profiles of prosocial behavior. Eighty‐seven 18‐month‐olds were observed in tasks assessing sharing with a neutral adult, instrumentally helping a neutral adult, and instrumentally helping a sad adult. Maternal mental state language (MSL) and maternal sensitivity were also assessed. Despite differing motivational demands across tasks, we found consistency in children's prosocial behavior with three latent classes: no prosocial behavior, moderate prosocial behavior, and frequent instrumental helping across emotional situations. Maternal sensitivity, MSL, and their interaction predicted toddlers' membership in the classes. These findings evidence moderate consistency in early prosocial behaviors and suggest that these capacities are motivated in early relationships with caregivers.